2023
DOI: 10.1002/vms3.1174
|View full text |Cite
|
Sign up to set email alerts
|

First detection of hepatitis E virus in dromedary camels from Iran

Abstract: Background: Hepatitis E virus (HEV) genotype 7 is a zoonotic disease detected in dromedary camels.Hypothesis/objectives: The consumption of camel meat and dairy products, the abundance of dromedary camels in Southeast Iran and the import of camels from neighbouring countries to Iran made the researchers investigate the infection rate of camels by the virus. Animals: A total of 53 healthy camels in Southeast Iran (Sistan and BaluchistanProvince) tested for HEV RNA.Method: A total of 17 blood samples and 36 live… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
2
2
0
Order By: Relevance
“…In perfect accordance with the outcomes of our work, the impact of camels’ sex on HEV seropositivity has been well established in favor of males by El-Kafrawy et al ( 28 ) and Sarani et al ( 36 ). Conversely, in the studies by Li et al ( 29 ) and Ouoba et al ( 17 ), no statistically significant relationship between HEV seropositivity in camels and their sex was notified.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In perfect accordance with the outcomes of our work, the impact of camels’ sex on HEV seropositivity has been well established in favor of males by El-Kafrawy et al ( 28 ) and Sarani et al ( 36 ). Conversely, in the studies by Li et al ( 29 ) and Ouoba et al ( 17 ), no statistically significant relationship between HEV seropositivity in camels and their sex was notified.…”
Section: Discussionsupporting
confidence: 92%
“…This effect could not be ascertained by Ouoba et al ( 17 ), who observed a random distribution of HEV-positive camels among the three countries of their study. We confirmed in our work an impact of province (county) of origin on the spread of this infection; however, similar surveys are unavailable to examine it, except the paper published by Sarani et al ( 36 ) in Iran. Remarkably, geographic differences in HEV seroprevalence rates of cattle within different localities or provinces of the same country have already been demonstrated in Egypt and China ( 37 , 38 ).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations